Cultural Identity and Performing Context of Dangaura Tharu Folk Dances - Kharel, Megh Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This article in the first sectiondiscussesabout the features and the theoretical aspects of folk dance in general. Folk dances of Dangaura Tharus show the vibrant life of the community that enhances the ethnic and national consciousness as well as their identity and representation in the surrounding of diverse ethnic and caste people of Nepal. In the second section, the study highlights the classification of notable folk dances in their performing contexts. Relying on their performing context, the research also exploresfolk dances of Tharus related to certain ritual songs, festival songs, common songs and working period songs. On the one hand, their folk dances have the cultural root of society evidently features its socio-cultural aspect that reveals the companionship, friendship and affection among the members of Tharus. On the other, the appraisal of the musical dances underscores the non-classical sites of vernacular expression with their ancestral, familial and local interaction. Therefore, the study concludes that tradition of performing folk dances in different contexts underpins the socio-cultural activity and communication of folk life to foster their identity, representation and cultural memory.